THE ROLE OF HUMAN RESOURCE MANAGEMENT IN SERVICE QUALITY IMPROVEMENT OF HOTEL BUSINESSES - Maria Greasidou; Ioannis Valachis (ENLIGHTENING TOURISM. A PATHMAKING JOURNAL, 2022)
In order a hotel business to achieve a long-term quality performance, it should train, empower and actively involve the employees in the service process. Therefore, the involvement of Human Resourse Management (HRM) department is imperative. The purpose of this study is to explore the level that HRM basic approaches are applied by hotels, particularly those fundamental requirements that might enhance quality service provision. Furthermore, the paper is examining the individual and unique characteristics of the hotel units, such as size, categorization etc., in an effort to reveal possible diversions and correlations according to the HRM implemented philosophy. According to the research findings, the examined hotels adopt a range of agreed HR policies and practices that are more likely to create organizations aiming to compete on the basis of high-quality services. Moreover, the hotels that apply greater HRM principles are those of great capacity. This can be explained due to the large number of hotel employees; their number, along with the fact that hospitality is a labour-intensive industry, necessitates HRM practices to play an important role in service quality provision. One more interesting finding arising from this research is that the category of the hotel does not play an important role at the degree that a hotel applies HRM best practices.